Artistic rendering of epileptic seizures - Tham, Yiling (2014)
Epilepsy is a chronic non-communicable disorder of the brain, characterized by seizures that occur at unpredictable moments. Epileptic seizures also known as fit, are short episodes of irregular or excessive brain activity. It was reported by the World Health Organization (WHO) states that more than 50 million people worldwide are suffering from epilepsy. Epilepsy also affects everybody, regardless of age, gender or race. The usual methods of representing epilepsy are the electroencephalography (EEG) graphical representations and these graphs are normally understood by medical professionals only. In addition, not everyone has experience with epilepsy and thus it is important to raise the awareness and understanding of this critical condition.